Mediation as an Alternative Dispute Resolution Mechanism in the UAE Construction Industry - Alhadhrami, Mohamed Abdulla Bamakhrama (2013)
This dissertation investigates whether mediation is a proper dispute resolution mechanism for the UAE construction Industry or not. Mediation as an alternative dispute resolution is a form of settlement process that is flexible, fast and the parties in disputes are not at risk of being bound by an unfavourable outcome by a third party's decision. Mediation has been critically evaluated against the UAE culture and legal system and its possibility of accommodating mediation as a system of alternative dispute resolution. Also, it has been assessed on the possibility of using mediation as means of alternative dispute resolution mechanism in the construction industry of the UAE with a comparative analysis with other alternative disputes resolution methods. Furthermore, mediation has been evaluated for a proposition of a model for the implementation of mediation methods in the construction industry of the UAE. The approach of the research used in this dissertation was deductive research. It has been conducted to provide a deduction of how well mediation can be used in lieu of litigation and other options that exists in dispute resolution. The research was conducted through a survey and interview. Data collected included data from a sample of two authorities in the field of construction in the UAE. In addition, a data was collected from a survey that has been conducted from 20 people in the field of construction in the UAE. The conclusion showed that Speed, affordability and flexibility are important aspects of dispute resolutions in the construction industry. This makes litigation an inappropriate method to dealing with construction disputes and the approach of using mediation is a much more acceptable method for dealing with in the construction sector and the construction industry. Mediations and the mediation industry of the UAE is one that has potential and that the government should make arrangement to promote mediation in the construction industry. The main arrangements are to integrate international and local standards into mediation, the UAE's judiciary system must accept and recognize mediation, develop and train local mediators, putting a framework of ethics and standards in place for the mediators to follow, creating a regulatory authority to supervise the activities of the mediators and setting up a committee to examine and evaluate the activities of the mediations in the country's construction industry.